ANTIBACTERIAL ACTIVITY OF Xetospongia sp. AND Spongia sp. SPONGE EXTRACT AGAINST PATHOGENIC BACTERIA FROM THE WATERS OF PAHAWANG ISLAND, LAMPUNG - Anma Hari Kusuma; Berta Putri; Eko Efendi; Tiara Safitri; Siska Hidayah (Universitas Mataram, 2025)
Sponges are marine benthic invertebrates from the Porifera phylum that have bioactive compounds that can function as antibacterials. The purpose of this study was to compare the extracts of sponges of the Xetospongia sp. and Spongia sp. against pathogenic bacteria. This study was conducted in May-November 2025. Samples of sponges of the Xetospongia sp. and Spongia sp. taken from the waters of Pahawang Island were extracted using methanol, ethyl acetate and hexane. The results showed that the morphological characteristics the Xetospongia sp. had a rough body surface with a rounded shape and reddish color while the Spongia sp. type had a soft body surface with crusts and a dark black color. The yield of sponge extract using ethyl acetate was greater than using methanol and hexane. The antibacterial activity of sponge extracts against pathogenic bacteria of the Xetospongia sp. used hexane while the Spongia sp. used methanol.